THE PERCEPTION OF ENGLISH TEACHERS TOWARD MERDEKA BELAJAR CURRICULUM IN SMPN 4 MUARA BUNGO - Dea Tasya Sabila (Universitas Muhammadiyah Muara Bungo, 2023)
This research was about current topics with the implementation of the new curriculum implemented in Indonesia, especially in Muara Bungo. Namely Merdeka belajar curriculum that was implemented. The purpose of this study is to know the teacher’s perception toward Merdeka Belajar Curriculum. The Merdeka belajar curriculum is a new curriculum that was implemented at SMPN 4 Muara Bungo especially in grade 7. This type of research is a research design that applies Descriptive qualitative with Qualitative Methods. The participants in this study were English teachers in SMPN 4 Muara Bungo. The sampling technique was purposive sampling. The instrument used in this study was open-ended-questions and semi structured for interviews. The result show of the study reveals that teachers have positive and negative perception on the implementation of Merdeka belajar curriculum. There are several factors that influence the teacher's positive perception of the implementation of Merdeka belajar Curriculum, namely teacher teaching experience, educational background, and teacher training. But the negative perceptions that teachers have was in the form of a lack of teaching media, lack of support from schools in fulfilling teaching media that can help the learning process, and also teachers' difficulties in grouping students based on their hobbies and characteristics.